Magical Interpellation: An Althusserian Analysis of Ideological Control in Lev Grossman's The Magicians - Caleb Imdad, Jonathan; Syeda, Fatima (Journal of Research in Humanities, 2025)
This paper applies Louis Althusser’s Marxist theoretical perspective of Ideological State Apparatuses (ISAs) as instruments of ideological control to examine Lev Grossman’s nove The Magicians. Through an analysis of Brakebills College for Magical Pedagogy as a fictional ISA, the study explores the interpellation of characters and readers, raising questions about power, resistance, and subjugation within the fantasy genre. The Magicians not only reflects systems of power in the real world but also critiques these same structures, inviting readers to engage critically with escapism, identity formation and the function of fantasy in cultural and ideological contexts. This analysis develops a framework for understanding popular culture's role in ideological reproduction and its potential for contesting these processes. The study concludes that The Magicians is both a reflection of, and a challenge to, contemporary cultural ideologies.